Investigating mindfulness as the potential mediator between NBPA and wellbeing: an ecological dynamics interpretation - Chouja, Tarek Michael; Brymer, Eric; Del Vecchio, Luke (Frontiers in Psychology, 2025)
The wellbeing benefits of Nature Based Physical Activities (NBPA), also known as Green Exercise, are well documented. However, little is known about how the wellbeing benefits come about. Ecological dynamics (ED) theory suggests that NBPA facilitates mindfulness, which ultimately improves wellbeing. This scoping review systematically reviewed literature to examine how NBPA facilitates mindfulness, which contributes to wellbeing outcomes. It also evaluated the usefulness of the Ecological Dynamics (ED) framework in interpreting these findings. This review uniquely contributes to the emerging field of NBPA by applying the ED framework to understanding how NBPA might facilitate mindfulness in the emergence of wellbeing outcomes. Given the limited literature available, a scoping review was the preferred method. All searched articles were peer-reviewed, empirical articles, and full text in English published between Jan 2002 and Sep 2024. After an initial search of 1,571 articles across 14 databases, nine studies were included in the scoping review for complete analysis. Findings indicated that NBPA facilitates mindfulness and this connection produces wellbeing outcomes for individuals with little to no nature based or mindfulness experience. The review has highlighted a clear gap and opportunity in the emerging field of NBPA and mindfulness interventions for wellbeing outcomes for the general population and in environments other than natural forests like rural parks.